Investigating Attitudes towards Refugee Students based on Several Variables: Revised Version of Refugee Student Attitude Scale - Ahmet Göçen; Ragıp Terzi; Bilal Altun (Sakarya University Journal of Education)
The immigration movement sometimes causes a sudden demographiccomplexity for countries and then leads to the development and implementationof urgent public policies. The most important one of these urgent policy areasin the long term is education. Countries, especially in cases of foreign migration,international aid organizations provide food, shelter, heating, and so on atthe first place, and then aim to ensure linguistic, cultural, and socialcohesion of migrants. At this stage, the contribution of hosting teachers andschool administrators to attitudes towards migrants and inclusive educationpolicies is a key to the efficient functioning of the process. In this study,attitudes towards refugee students of teachers from Sanliurfa, one of Turkey'smost populated-refugee cities, is investigated based on several variables. Forthe purpose, Refugee Student Attitude Scale (RSAS), developed by Sağlam andKanbur (2017), was updated via EFA and CFA analyzes and then analyzed byMANOVA. It was found that attitudes of the young female teachers towards “communication”and “adaptation” were higher than male teachers; in contrast, male teachersworking for long years were better in their “communication” and “competency”attitudes than female teachers. Furthermore, teachers with many years ofteaching experience who have refugee students in their classs have higher in“communication” and “adaptation” attitudes.